Langue et pouvoir en Afrique sur quelques paradoxes de la politique linguistique française depuis la periode coloniale - Riesz, János (Africana Studia, 2020)
The expansion policy of the French language in the French speaking countries builds on a strangc paradox. The Language was to be used only as a means of communication, and never, under any circunstance, should other people be allowed the opportunity to know both its essence and history. A good writer or a good philosopher of the French language can be nothing else but French, for no other people have or can acquire the right competence as far as the language is concerned.